The Mediating Role of Job Satisfaction in Career Development and Employee Performance - Billive Maitimu; Agusthina Risambessy; Felix Chandra (West Science Interdisciplinary Studies, 2026)
This study aims to analyze the mediating role of job satisfaction in influencing career development on employee performance at PT Bank Maluku Malut, Ambon Main Branch. The population in this study was all 55 employees of PT Bank Maluku Malut, Ambon Main Branch. The research sample consisted of 48 respondents selected using purposive sampling technique. Data analysis was conducted using SmartPLS 4 application through testing the measurement model (outer model) and structural model (inner model). The results of the study indicate that: (1) career development does not have a significant effect on the performance of employees of PT Bank Maluku Malut, Ambon Main Branch; (2) career development has a positive and significant effect on job satisfaction, which shows that opportunities and clarity of career development can increase employee job satisfaction; (3) job satisfaction has a significant effect on employee performance, so that the higher the job satisfaction, the better the performance produced; and (4) job satisfaction is proven to play a role as a mediating variable in the influence of career development on employee performance. This shows that career development does not directly improve performance, but through increasing job satisfaction which then encourages employees to produce more optimal performance.